Preliminary study on implantable inductive-type sensor for continuous monitoring of intraocular pressure - Kim, Yong Woo; Kim, Mi Jeung; Park, Ki Ho; Jeoung, Jin Wook; Kim, Seok Hwan; Jang, Cheol In; Lee, Soo Hyun; Kim, Jae Hun; Lee, Seok; Kang, Ji Yoon (WILEY, 2015)
Background: This study aims to validate the performance and biocompatibility of an implantable inductive-type sensor for continuous monitoring of intraocular pressure (IOP) Methods: The sensor is composed of a top layer integrated with an inductor and capacitor circuit, and a bottom layer integrated with ferrite. With IOP change, the sensor's bottom layer is mechanically deflected, which changes the distance between the bottom-layer ferrite and top-layer inductor, resulting in an alteration of inductance magnitude and the resonant frequency (RF). In-vitro measurement was conducted via air pressurization in a sealing jig (n = 3). Subsequently, the sensor was implanted into the anterior chamber of a rabbit eye. In-vivo measurement was performed while the IOP was elevated by infusion of balanced salt solution (BSS, 6 mu L/min). Smaller-sized sensors later were implanted into two rabbit eyes, which were microscopically examined at 2, 4 and 8 weeks post-implantation. The eyes were then immediately enucleated for histological examination. Results: The in-vitro measurement showed a significant RF shift as pressure in the jig was increased from 0 mmHg to 60 mmHg (average initial frequency: 10.86 MHz, average shift: 403 kHz). The in-vivo measurement also showed an RF decrease, from 12.80 MHz to 12.67 MHz, as the pressure was increased from 10 mmHg to 20 mmHg. Microscopic in-vivo evaluations and histological exams, performed at intervals up to 8 weeks post-implantation, showed no evidence of significant inflammation or deformity of the ocular-tissue structures. Conclusions: The implantable inductive-type IOP sensor demonstrated wireless pressure-sensing ability and favourable biocompatibility in the rabbit eye.
Keywords: VISUAL-FIELD LOSS; ADVANCED GLAUCOMA INTERVENTION; OPEN-ANGLE GLAUCOMA; RISK-FACTOR; TELEMETRY; PATTERN; PROGRESSION; POSITION; EYE